Praktik Jual Beli Online pada Akad Salam pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam - Jumarnawati Jumarnawati; Ahmad Syahrizal (ARZUSIN, 2025)
The development of the digital era has driven a significant transformation in economic activity through the use of e-commerce, which has changed transaction patterns between consumers and business actors, so that in the context of Islamic economics it is necessary to apply contracts that comply with Islamic principles in order to avoid elements of injustice and ambiguity. This study aimed to analyze online buying and selling practices using the akad salam conducted by students of the Faculty of Islamic Economics and Business. The research employed a qualitative approach with a field research design, involving 20 students as informants selected through purposive sampling. Data were collected through in-depth interviews and documentation, and were then analyzed using qualitative descriptive techniques. The results show that students’ online buying and selling practices generally reflect the application of the akad salam, particularly in terms of advance payment, clarity of product specifications, and agreed timing and mechanisms for product delivery. Transactions are conducted through various digital platforms and social media by utilizing non-cash payment systems and, in general, already fulfill the pillars and conditions of sale in Islam, as well as sharia business principles such as honesty, justice, product permissibility, and a spirit of mutual assistance, although several obstacles in technical implementation remain. These findings contribute to strengthening contemporary fiqh muamalah studies in the context of e-commerce and underscore the importance of enhancing literacy on sharia contracts among students as prospective Islamic economic actors in the digital era.